2023
DOI: 10.3390/ijms24129921
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the MUFA–Cancer Connection: Insights from Endogenous and Exogenous Perspectives

Abstract: Monounsaturated fatty acids (MUFAs) have been the subject of extensive research in the field of cancer due to their potential role in its prevention and treatment. MUFAs can be consumed through the diet or endogenously biosynthesized. Stearoyl-CoA desaturases (SCDs) are key enzymes involved in the endogenous synthesis of MUFAs, and their expression and activity have been found to be increased in various types of cancer. In addition, diets rich in MUFAs have been associated with cancer risk in epidemiological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 225 publications
0
6
0
Order By: Relevance
“…Additionally, two separate studies found that dietary MUFAs were linked to a reduced risk of pancreatic cancer ( Nkondjock et al, 2005 ; Banim et al, 2018 ). The potential antitumor effects of MUFAs may be attributed to their antioxidant properties, capacity to reduce chronic inflammation, and cholesterol-lowering properties ( Farag and Gad, 2022 ; Wan et al, 2022 ; Guo et al, 2023 ). Furthermore, in the present NHANES observational study, after adjusting for potential confounders, the authors observed a protective effect of a high-MUFAs diet against GC, consistent with the findings of the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, two separate studies found that dietary MUFAs were linked to a reduced risk of pancreatic cancer ( Nkondjock et al, 2005 ; Banim et al, 2018 ). The potential antitumor effects of MUFAs may be attributed to their antioxidant properties, capacity to reduce chronic inflammation, and cholesterol-lowering properties ( Farag and Gad, 2022 ; Wan et al, 2022 ; Guo et al, 2023 ). Furthermore, in the present NHANES observational study, after adjusting for potential confounders, the authors observed a protective effect of a high-MUFAs diet against GC, consistent with the findings of the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is still unclear how OA activates Cdc42, it is wellrecognized that Cdc42 can be activated by a number of cell surface receptors, such as G protein coupled receptors (GPCRs), receptor tyrosine kinases (RTKs), and integrin receptors, which converge on Cdc42 by activating specific GEFs [64]. OA is known to be involved in activating GPR40/120 [13,41,66], insulin receptor (a member of RTK family) [67], and integrin receptor signaling [13,42,43], which, in turn, can potentially activate Cdc42 via downstream GEFs. Moreover, lipid modifications play an important role in the regulation of Cdc42 activity [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of olive oil is a defining feature of the Mediterranean diet, renowned for its health-promoting attributes and traditionally associated with protective effects against cardiovascular diseases, diabetes, obesity, and cancer [7][8][9][10][11][12]. MUFA, particularly OA, has been the subject of extensive research exploring its potential impact on cancer, including 2 of 18 breast cancer [13]. However, the outcomes of these investigations remain inconclusive, yielding both pro-cancer and protective effects [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oleic acid (OA), a ω-9 fatty acid, promotes the proliferation of breast cancer cells by activating specific signaling pathways linked to G protein-coupled receptors (GPR) 40 and 120 [66,67] and a network of signaling pathways involving PKC, ERK, EGFR, MMP, PI3K/Akt, and PLD2/mTOR [68,69].…”
Section: Cancer Cellsmentioning
confidence: 99%